(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2018)
Background: Multiple Myeloma (MM) is a neoplasm of B cell lineage characterized by excessive proliferation of abnormal plasma cells, secreting abnormal immunoglobulin causing monoclonal gammopathy which can be detected by the presence of M protein in serum and urine electrophoresis. Aim: Present study is aimed to detect and quantify monoclonal gamma globulins by SPEP and IFE in suspected case of MM and other plasma cell dyscrasias and also to find out the discrepant findings between SPEP and IFE. Methods: A retrospective observational study was carried out on clinically highly suspected cases of Multiple Myeloma (MM) presenting with backache, asthenia and generalized weakness at Armed forces Institute of Pathology(AFIP), Dhaka cantonment from January 2015 to July 2016. A total of 140 blood samples were collected and subjected to serum protein electrophoresis (SPEP) and Immunofixation electrophoresis (IFE). IFE identifies the type of heavy (IgG, IgM or IgA) and light chain (either kappa or lambda in suspected cases of MM Results: Out of 140 cases, SPEP identified monoclonal band in 62 cases and either non-specific findings or polyclonal band in 78 cases. At the same time immunofixation electrophoresis (IFE) which was done on all samples detected another 14 cases of M-band in addition to earlier 62 cases of monoclonal gammopathy by SPEP. Among 140 cases, SPEP detected M-band in 62 cases, whereas IFE identified monoclonal band in 76 cases. So in the remaining 14 cases (10%) small sharp spikes of monoclonal band was found only by IFE whereas SPEP failed to detect those 14 cases. Conclusion: SPEP is an easy to perform laboratory test which can be used for detection and quantification of monoclonal gammopathy but there is some limitation in detecting monoclonal band by SPEP. IFE is more sensitive to detect the monoclonal band than SPEP. So both SPEP and IFE should be done simultaneously for precise diagnosis of MM and related disorders. J Bangladesh Coll Phys Surg 2018; 36(3): 95-100